Screening for possible oligogenic pathogenesis in Chinese sporadic ALS patients. Issue 5 (3rd July 2018) - Zhang, Hang; Cai, Wanshi; Chen, Siyu; Liang, Jialong; Wang, Zhanjun; Ren, Yuting; Liu, Wenxiu; Zhang, Xiaolan; Sun, Zhongsheng; Huang, Xusheng
Abstract: We investigated all coding regions of 17 known amyotrophic lateral sclerosis (ALS)-related genes in 311 sporadic ALS patients who were of Chinese ancestry using next-generation sequencing technology. All nonsynonymous variants identified were confirmed by Sanger sequencing. 29 (9.32%) patients harbored at least one pathogenic or likely pathogenic variants. Nine (2.8%) patients harbored two or three variants which frequency <1% in population databases that may be related to oligogenic pathogenesis. A higher allele frequency was observed in East Asian than in European patients for the majority variants identified in this screening, which may indicate that genetic factors are responsible for the different clinical characteristics between Chinese and European ALS patients. Our study reports the results of extensive genetic screening and is the first to investigate the possible oligogenic pathogenesis in Chinese sporadic ALS patients. These findings are useful for exploring ALS pathogenesis and treatment strategies.